Problematika Gugatan Perdata Terhadap Ahli Waris Pelaku Tindak Pidana Korupsi - AR, Zulkifli; Rosalina, Maria; Jehan, Ahmed (Universitas Islam Sumatera Utara, 2023)
Corruption crimes that occur in Indonesia are still a serious problem that can result in losses to state finances that can affect the country's ability to fulfill the rights of its people. The process of recovering state financial losses on the one hand is part of the examination of criminal cases as in the case of additional crimes is of course very effective, but in certain cases as stipulated in Article 32 paragraph (1) (2), Article 33, Article 34 and Article 38 C It is no longer possible to carry out the criminal process under the Corruption Crime Law, so in this case the civil law enforcement process needs to be upheld even though it has to go a long way as a lawsuit in the civil procedural law stipulated in the HIR and Rbg.The Attorney General's Office as the State Attorney General has the authority to file civil lawsuits for state losses resulting from the actions of the perpetrators of corruption against their heirs. For the effectiveness of the civil lawsuit process regulated in the HIR and Rbg in terms of recovering state losses, it is deemed necessary for the Supreme Court to respond by making complementary rules to the formal law in accordance with the principle of justice that is carried out quickly, simply and at low cost as stipulated in the Law. Law Number 48 of 2009 concerning Judicial Power.Keywords: Civil Lawsuit, Heirs, State Attorney, Corruption Crime.